IHC characteristics of stem cell markers in PDAC with different degrees of differentiation - V. Kabachenko; M. Shishkin (Journal of Education, Health and Sport, 2022)
Introduction. Cancer stem cells (CSCs) play a key role in the development, progression and metastasis of cancer. Cell surface markers, in particular CD44 and EpCAM, are used to identify CSCs. Marker expression patterns depend on the stage of progression and differentiation. Materials and methods. Histopathological and IHC studies of 49 cases of the pancreas ductal adenocarcinoma (PDAC) of G2, G3 degrees of differentiation. Results of IHC reactions with antibodies against CD44 and EpCAM were estimated by photo digital morphometry and were expressed in immunostained cells relative area (%). Results. Adenocarinoma of the pancreas is characterized by a moderate level of expression of cell surface markers CSC - CD44 and EpCAM. The expression level of CD44 in the І gr. - Me = 34.11% (Q1 = 31.03; Q3 = 38.39), in the II gr. - Me = 43.17% (Q1 = 39.83; Q3 = 47.04), significantly higher than in the I gr. (Kruskal-Wallis test p<0.05). The expression level of EpCAM in the I gr. - Ме=26,10% (Q1=20,42; Q3=31,89), in the II gr. - Ме=31,07% (Q1=27,03; Q3=34,00) (p>0,05). In both groups, the relative area of EpCAM was significantly lower than CD44 (Kruskal-Wallis test p<0.05). Correlation analysis (Pearson's ratio) showed a weak negative relationship between markers at G2 (r = -0.17, p>0.05), at G3 - a weak positive (r = + 0.06, p>0.05).